(untitled) (Journal of actual problems of jurisprudence, 2024)
In the era of digital transformation, the landscape of securities is undergoing profound changes. Our research focuses on exploring the potential implementation of digital shares in the Republic of Kazakhstan, delving into the intricacies of issuing and placing shares through tokenization to secure funding for companies. Employing a methodology encompassing analysis, comparative jurisprudence, legal modeling, and a historical-comparative approach, our study has identified key trajectories for the evolution of digital shares in Kazakhstan. Additionally, we have conducted a comprehensive comparison of the processes involved in Security Token Offerings (STO) and Initial Public Offerings (IPO). This work underscores the significance of tokenizing shares as a pivotal tool for attracting financing and executing Kazakhstan’s strategy for digitalization. The research conducted serves as a substantial contribution to the field of knowledge concerning digital shares and financial law. Furthermore, it holds practical value for informing the development of legislation and infrastructure aimed at facilitating the digitalization of shares within the Kazakhstan context. Keywords: digital shares, tokenization of shares, digital economy, securities, blockchain, civil law.